Teaching and Learning Analytics to Support Teacher Inquiry - Hachem AlaouiHaroun, Moulay; HACHEM, El-Kaber; Ziti, Cherif (International Journal of Engineering and Technology, 2018)
Teaching In this article we are going to introduce the concept of reflective practice as an important instrument for practice-based professional development, as well as organizational learning and improvement; and define the concept of teacher inquiry as a key method for data-driven reflection on-action, related to the process where teachers build useful knowledge about teaching and learning through the deliberate and systematic study of their own practice. It also discusses some Teaching Analytics tools in our platform ASTEMOI to show how teacher can reflect on their teaching design. This study employs focus group as qualitative research methodology to discuss benefits of Teacher inquiry in the help of data-reflection on-action.Â Â